Government responses to COVID-19 and impact on GBV services and programmes: comparative analysis of the situation in South Africa, Kenya, Uganda, and Nigeria - Neetu A. John; Paul Bukuluki; Sara E. Casey; Dhruvi B. Chauhan; Moriam O. Jagun; Nicoletta Mabhena; Mary Mwangi; Terry McGovern (Sexual and Reproductive Health Matters)
As governments impose restrictive policies to contain infectious disease outbreaks, pre-existing gender-based inequalities are often exacerbated, increasing the risk of gender-based violence (GBV). Despite international guidance on the need for continued provision of GBV services during emergencies, governments often de-prioritise GBV services and programmes. We conducted a rapid assessment in South Africa, Kenya, Uganda, and Nigeria to examine the impact of COVID-19 policies on the availability of GBV prevention and response services. The study team interviewed 80 stakeholders representing different GBV services in the four countries. The interviews revealed strikingly similar government mis-steps that disrupted the availability of comprehensive GBV services. In all four countries, the government’s failure to exempt the provision of multi-sectoral GBV services from initial lockdown restrictions led to confusion and disrupted the provision of critical GBV services such as clinical management of rape, legal and judicial services, psychosocial services, availability of shelters, and community-based prevention activities. The government’s imposition of curfews, stay-at-home orders, and transportation restrictions further diminished access to services. Governments must strengthen currently available GBV prevention and response services and be better prepared for future pandemics. Following international guidelines, governments should deem GBV services as essential from the beginning with clear implementation plans. Governments must invest in community-based solutions and the expansion of digital tools to ensure everyone, especially those likely to be structurally excluded, have access to critical services during an emergency.